Two-pore channels in MR1-dependent presentation of Mycobacterium tuberculosis infection. - Elham Karamooz; Se-Jin Kim; Jessie C Peterson; Allison E Tammen; Shogo Soma; Aviva C R Soll; Erin W Meermeier; Sharon Khuzwayo; David M Lewinsohn (PLoS Pathogens)
MR1 is a ubiquitously expressed MHC-Ib molecule that presents microbial metabolites to MR1-restricted T cells, but there are differences in the antigen presentation pathway of an intracellular microbe compared to exogenously delivered antigen. We have shown the importance of endosomal trafficking proteins in MR1-dependent presentation of Mycobacterium tuberculosis (Mtb) infection. Two pore channels (TPCs) are endosomal calcium channels that regulate endosomal trafficking. Due to their location on endosomes, we hypothesized that TPCs could be required for MR1-dependent presentation of antigens derived from the intracellular microbe Mtb. We found that TPC1 is critical for the presentation of Mtb infection by MR1; inhibition of TPCs had no effect on MR1 presentation of exogenously delivered antigens, HLA-B presentation, or HLA-II presentation. Finally, we found that the calcium-sensitive trafficking protein Synaptotagmin 7 was also key in the presentation of Mtb infection by MR1. TPC1 and Synaptotagmin 7 may be part of an endosomal pathway by which MR1 can sample intracellular mycobacterial infections.